2000
DOI: 10.1093/ps/79.11.1669
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental lighting on early semen production and correlated hormonal responses in turkeys

Abstract: Recent work at our institution on lighting turkey males for semen production and correlated changes in plasma luteinizing hormone (LH) and testosterone (T) are summarized in this paper. In sexually mature males, both LH and T are secreted in pulses, with a pulse of LH about 10 min prior to a pulse of T. Pulses of LH and T occurred about every 2 h and were equally distributed between the light (L) and dark (D) portions of a 14 h L:10 h D d. The pattern of secretion and overall concentrations of LH and T were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 57 publications
1
10
0
2
Order By: Relevance
“…Previous studies using commercial breeder turkeys revealed a high degree of sensitivity to photoperiod for TW [10,11], semen output [18], and circulating LH and testosterone concentrations [6][7][8][9]. The present results confirmed previous observations [10,11] that prepubertal male turkeys maintained under constant long days are precocious semen producers (26-29 wk) In .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Previous studies using commercial breeder turkeys revealed a high degree of sensitivity to photoperiod for TW [10,11], semen output [18], and circulating LH and testosterone concentrations [6][7][8][9]. The present results confirmed previous observations [10,11] that prepubertal male turkeys maintained under constant long days are precocious semen producers (26-29 wk) In .…”
Section: Discussionsupporting
confidence: 90%
“…In males from previously named species, LH and testosterone are discharged in pulsatile patterns during both the photophase and the scotophase of the nycthemere. Moreover, it appears that in mature male www.journals.elsevierhealth.com/periodicals/the Theriogenology 66 (2006) [851][852][853][854][855][856][857][858][859] turkeys, a pulsatile pattern of testosterone is maintained regardless of its baseline concentration, whereas the pulsatile pattern of LH is maintained only if associated with low plasma concentrations of both LH and testosterone [6,7]. Turkey males in semen production exposed to continuous or intermittent light regimes had minor differences in patterns of LH and testosterone secretion [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other positive functions such as host‐derived signals may stimulate the transformation. Possible host‐derived signals include puberty, although measurable levels of testosterone do not accumulate until week 19 (Bacon et al , 2000). Other signals could be derived from the expansion of the gut‐associated lymphoid tissue that occurs between 6 and 12 weeks of age and the concurrent increase in TCR1‐expressing T cells between 9 and 12 weeks (Befus et al , 1980; Lillehoj & Chung, 1992).…”
Section: Discussionmentioning
confidence: 99%